ENGLISH: PROPHET MUHAMMAD (PBUH) AS A MILITARY STRATEGIST: LESSONS FOR MODERN WARFARE - Hafiz Munir Ahmed khan; Abrar Hussain (دی اسکالر)
The present piece of writing discusses about the outstanding military tactics of Prophet Muhammad that are applicable to complexities of warfare in contemporary times. The prophet was not only a strategic genius but also tender-hearted military general who worked towards permanent peace. Besides winning many wars like Badr, Uhud and Khandaq due to good tactical thinking, he had understanding of human nature and life itself. This rapid adaptation time under dynamic circumstances, foreseeing the enemy’s tactics by a little insight and upliftment of soldiers through the idea justice as well as goals laid down by him is still relevant in present day military operations that were never religiously tolerant until they kill every single weak group’s member during which settling for peaceful coexistence has been defined over a long term. These principles are timeless in an intricate world with battles dominated patterns throughout its narrative history. they tell us that real battlefield leaders are not those who have great armies alone; they entail wisdom, moral principles plus everyone’s welfare. Through historical narratives this research aims at showing how today’s military leaders can derive inspiration from Prophet’s methods that lead them into victory as well as humanity.